The Added Benefit of Hybrid SPECT/CT in the Diagnosis of Bone Metastasis in Patients with Breast Cancer (Bangladesh Journal of Nuclear Medicine, 2015)
The purpose of this study was to investigate the additional benefit of single photon emission computed tomography/computed tomography (SPECT/CT) over whole-body planar bone scintigraphy (planar BS) and SPECT for the detection of bone metastases in breast cancer patients. Materials & methods: Of 112 consecutively examined patients with histologically confirmed breast carcinoma who underwent bone scintigraphy, 39 required further evaluation by SPECT/CT (n= 23) and SPECT alone (n = 16) because a definite diagnosis could not be established using whole body planar BS alone. The 23 SPECT/CT studies were retrospectively evaluated by two nuclear medicine physicians for planar BS and SPECT images, and one nuclear medicine physician and one radiologist for SPECT/CT on consensus. Each focus of abnormal tracer uptake was recorded for differentiating malignant from benign bone lesions. Clinical and imaging follow-up were used as a reference standard. Results: A total of 72 lesions were evaluated in 23 patients examined by three types of imaging modalities. In 57 of the 72 evaluated lesions, the results of planar BS, SPECT and SPECT/CT were concordant; 52 of the 57 lesions were interpreted as malignant and 5 lesions as benign by all modalities. In 15 of the 72 lesions, consensus reading of fused SPECT/CT images changed the image interpretation of 15 planar BS scans and 9 of the 15 SPECT scans: 7 lesions previously interpreted as benign (on both planar BS and SPECT) were re-classified as malignant and 8 lesions (8 by planar BS and 2/8 by SPECT) previously interpreted as malignant were reevaluated as benign. The highest diagnostic gain was in the thoracolumbar spine, thoracic cage & pelvis. The overall accuracy of SPECT/CT was significantly higher on a lesion-based analysis than planar BS and SPECT (100%vs 79%, p < 0.0001 and 100% vs 83%, p = 0.003). Compared to planar BS and SPECT, the results of SPECT/CT changed diagnosis or treatment in 5/23 patients (21.7%). 39 Conclusion: The hybrid imaging system with SPECT/CT is a feasible technique yielding coregistered dual-modality images. The addition of SPECT/CT improves the diagnostic accuracy for the correct interpretation of bony lesions in breast cancer patients undergoing bone scanning for metastases. SPECT/CT should be routinely used in the work up of postoperative breast carcinoma patients with simultaneous CT evaluation to identify metastatic lesions not detected on bone scintigraphy. DOI: http://dx.doi.org/10.3329/bjnm.v17i1.22490 Bangladesh J. Nuclear Med. 17(1): 38-49, January 2014